Matemática e educação matemática: a dinâmica de suas relações ao tempo do movimento da matemática moderna no Brasil - Duarte, Aparecida Rodrigues Silva (2007)
This assignment had as the main objective to investigate the dynamic of Mathematic and Mathematic Teaching relationship. Based on methodological presuppositions of Cultural History, the developed research requested the development of a study about the relationship between the dynamics of the academic culture and elementary school in the context of Modern Mathematic Movement (MMM) in Brazil, placed between the 1950 and 1980 decades. For the analysis of this matter, three characters were considered to be representative among the mathematic community from that time in reason of their expressive involvement in the MMM, they were: Omar Catunda, Benedito Castrucci and Luiz Henrique Jacy Monteiro. Thus, we decided to portray their scientific productions and proposals related to mathematics teaching, using didactic books, school document files and personal files, etc., as sources. The MMM was approached from its origins in the international scenario and from its insertion in the national education. This assignment emphasized in its conclusions how the relationship among mathematicians and mathematic teaching changes as time goes by and is established in a determinate historical period, besides that, in these dynamics relationships, academic culture feeds itself from elementary school and viceverse, causing a backward feeding relationship